Global prevalence of norovirus in cases of acute gastroenteritis from 1997 to 2021: An updated systematic review and meta-analysis. (December 2021) - Liao, Yingyin; Hong, Xiaojing; Wu, Aiwu; Jiang, Yueting; Liang, Yanhui; Gao, Junshan; Xue, Liang; Kou, Xiaoxia
Abstract: Background: The worldwide response towards the acute gastroenteritis epidemic was well known, but the absence of an updated systematic review of global norovirus epidemiology in cases of gastroenteritis existed. We aimed to conduct and update a systematic review and meta-analysis of studies assessing norovirus prevalence among gastroenteritis patients worldwide. Methods: Four databases (PubMed, EMBASE, Cochrane Library, and Web of Science) were searched for epidemiological papers from 2014 to 2021 which applied the PCR method to access the prevalence of norovirus in acute gastroenteritis patients more than a full year. Statistical analysis was conducted using R-4.0.0 software. Results: A total of 405 records with 842, 926 cases were included. The pooled prevalence of norovirus was 16% (95%CI 15, 17). Children under 5 years old were at a higher risk with norovirus. A higher prevalence was seen in South America (22%, 95% CI 18, 27), while other continents showed a similar result with the overall prevalence of norovirus. No association was found between national income level and norovirus prevalence. A gradient of decreasing prevalence was noticed from community (20%, 95% CI 16, 24) to outpatients (18%, 95% CI 16, 20) to hospital setting (included both in- and outpatients, 17%, 95% CI 16, 19) to inpatients (15%, 95% CI 13, 17). Conclusion: Norovirus were associated with 16% acute gastroenteritis globally. To fully understand the prevalence of norovirus worldwide, the continual surveillance of norovirus epidemics was required. Highlights: The pooled global prevalence of norovirus among acute gastroenteritis was 16% over the last 20 years. The infection rate stayed the same compared to the last decade. Norovirus should be included in continuous surveillance worldwide, especially in low-incoming countries.